Using a Hanging Ball For Primary School Students on Volleyball Down Passing - Purnomo, Deddy Hadi; Irvan Sir; Atmam Amir (ETDC: Indonesian Journal of Research and Educational Review, 2022)
The background for writing this article is the lack of interest and motivation in students' learning in participating in volleyball lessons, especially under passing. So students prefer other sports. The problem that is the center of attention in this study is whether down volleyball learning with a hanging ball can increase volleyball learning motivation in class VI students of MI Nurul Hidayah, Prajekan District, Bondowoso Regency. This study involved all sixth-grade students, with 16 students, consisting of 6 male students and 10 female students. The data collection technique used an action test assessment and observation sheets. In the first cycle, the results of filling out the questionnaire were conducted by Physical Education teachers. Judging from the results of the first cycle, there are 9 students (56.25%) who have completed and 7 students (43.75%) who have not completed, and in the second cycle, there are 14 students (87.5%) who have completed and there are 2 students (12.50%) who have not completed. This classroom action research was stopped in cycle II because it had reached the classical completeness criteria, namely 85% of the total number of students who had completed learning and were declared successful in improving the learning outcomes of Lower Passing with Hanging Balls in Class VI students of MI Nurul Hidayah.